2009
DOI: 10.1007/s00384-009-0801-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pT sub-classification in surgical pathology of colorectal cancer

Abstract: pT3 sub-classification was significantly associated with patient outcome. In contrast, pT2 and pT4 sub-classification did not show clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
2
37
1
1
Order By: Relevance
“…On subgroup analysis of these patients, MED consistently had a significant impact on postoperative recurrence rate along with the CEA level, which had been suggested as a useful prognostic factor in patients treated with preoperative CRT by several previous studies. 1,13,14,16 For T3 patients as a whole or T3 patients without preoperative CRT, lymph node metastasis was clearly the most important prognostic factor. However, interestingly, nodal status was not a significant prognostic factor for ypT3 rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On subgroup analysis of these patients, MED consistently had a significant impact on postoperative recurrence rate along with the CEA level, which had been suggested as a useful prognostic factor in patients treated with preoperative CRT by several previous studies. 1,13,14,16 For T3 patients as a whole or T3 patients without preoperative CRT, lymph node metastasis was clearly the most important prognostic factor. However, interestingly, nodal status was not a significant prognostic factor for ypT3 rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 there is a defect of the Pel at the mesenteric attachment; therefore, we undertook elastica staining on at least 1 whole section where the tumor was closest to the peritoneal surface to confirm the continuity of the Pel. the median numbers of h&e-and elastica-stained sections were 6 (range, 2-20) and 4 (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We defined cases with tumor invasion beyond the Pel as eli positive ( fig.…”
Section: Histopathologic Analysismentioning
confidence: 99%
“…the prognosis of patients with pt3 disease varies, which may be explained by differences in the depth of tumor invasion. [6][7][8] nevertheless, although it has been suggested that pt3 disease be subclassified, it currently remains 1 category. the peritoneal elastic lamina (Pel) is a component of the normal intestinal wall and can be identified histologically by elastica staining.…”
mentioning
confidence: 94%
“…Pollheimer et al [10] previously reported on pT2 rectal cancer cases, but they made only 2 classifications, and the classifications themselves were not detailed. The main finding of this retrospective study is that the lateral pelvic lymph node metastasis of pT2 colorectal cancer depends on the depth of vertical invasion, and this is analogous to the findings obtained for pT1 and pT3 cancers.…”
Section: Discussionmentioning
confidence: 99%